en.wikipedia.org/wiki/Mathematical_fallacy

In mathematics, certain kinds of mistaken proof are often exhibited, and sometimes collected, ... 1 Howlers; 2 Division by zero; 3 Multivalued functions; 4 Calculus; 5 Power and root. 5.1 Positive and negative roots; 5.2 Squaring both sides of an ...

mathforum.org/library/drmath/view/56734.html

Date: 11/19/95 at 17:12:23 From: Doctor Ken Subject: Re: 1+1 = 3 ? Hello! Let me say first of all that there is no real proof for the statement 1 + 1 ...

www.quora.com/How-can-you-prove-that-1+1-3

First of all, let me tell you that there is no real proof for the statement 1 + 1 = 3. You cannot use correct mathematics to prove an incorrect statement. However, there ...

puzzling.stackexchange.com/questions/5656/when-does-11-3

warspyking. 6,815445117. asked Nov 27 '14 at 19:04. josh. 15113 ... According to an old joke, this is true for extremely large values of 1 – Julian Rosen Nov 27 ... Now since a=b (the starting point of this proof), we can write this as: a+1=2a+1.

brilliant.org/discussions/thread/proof-that-1-1-and-1-3

Proof that -1 = 1 and 1 = 3. This image was sourced and then altered from the NASA image archive. The chimpanzee pictured was named Ham the Astrochimp.

math.stackexchange.com/questions/278974/prove-that-11-2

I'm not asking for a proof, but rather for some outline what one would consider to make ... Usually, it is defined to be that 2:=1+1, 3:=1+1+1, etc.

answers.yahoo.com/question/index?qid=20090801020846AAyCpa1

1 = 1 41 – 40 = 61 – 60 16 + 25 – 40 = 36 + 25 – 60 4² + 5² – 2 * 4 * 5 = 6² + 5² – 2 * 6 * 5 (4 – 5)² = (6 – 5)² 4 – 5 = 6 – 5 4 = 6 2 = 3 1 + 1 = 3. Regards.

www.quickanddirtytips.com/education/math/how-to-prove-that-1-2

May 16, 2014 ... What if I was to tell you that I could prove that 1 + 1 is actually equal to 1. And that .... Audio. 3 Frequently Asked Questions About Math Puzzles.

www.math.toronto.edu/mathnet/falseProofs/first1eq2.html

May 26, 1998 ... (IMAGE) Go forward to 1=2: A Proof using Complex Numbers ... The Fallacious Proof: Step 1: Let a=b. Step 2: Then (IMAGE) ,; Step 3: (IMAGE) ...